Colonic response to laxative ingestion as assessed by MRI differs in constipated irritable bowel syndrome compared to functional constipation - Lam, C.; Chaddock, G.; Marciani, L.; Costigan, C.; Paul, J.; Cox, E.; Hoad, Caroline; Menys, A.; Pritchard, Susan E.; Garsed, K.; Taylor, S.; Atkinson, D.; et al. (Wiley, 2016)
Background